1986
DOI: 10.1203/00006450-198612000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Epidermal Growth Factor and Artificial Feeding in Suckling Rats

Abstract: ABSTRACT. To evaluate the effects of epidermal growth factor (EGF) in dietary milk, a new method of delivering an artificial (EGF-deficient) formula was developed using 42 rat pups, 1-14 days of age. In a second study the effect of EGF was evaluated in suckling rats from 3-11 days of age: group 1, mother-fed; group 2, mother-fed plus daily injections of EGF (0.1 hg/g body weight); group 3, artificial milk fed with added EGF (62 ng/ml); and group 4, artificial milk fed without EGF. Each group consists of nine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Sixty newborn male and female rat pups from nine litters were randomly assigned to one of two groups: in the first group, rats were fed adequate amounts of formula per gavage calculated to provide a daily energy intake of 500 kcal/kg as described previously in more detail (24,30). In the second group, rats suckled ad libitum by the dam and were sham intubated every 6 h. An additional group of 17 rat pups were studied immediately after delivery and served as newborn controls.…”
Section: Animalsmentioning
confidence: 99%
“…Sixty newborn male and female rat pups from nine litters were randomly assigned to one of two groups: in the first group, rats were fed adequate amounts of formula per gavage calculated to provide a daily energy intake of 500 kcal/kg as described previously in more detail (24,30). In the second group, rats suckled ad libitum by the dam and were sham intubated every 6 h. An additional group of 17 rat pups were studied immediately after delivery and served as newborn controls.…”
Section: Animalsmentioning
confidence: 99%
“…To our knowledge, IGF-I is the only growth factor known to induce linear growth of the adult small bowel. While EGF injection has been reported to increase small intestinal length in suckling rats (Moore et al, 1986), a similar response has not been reported in normal or gut-resected adult rats. Our study did not identify the mechanism of IGFinduced linear growth of the small bowel.…”
Section: Discussionmentioning
confidence: 76%
“…It is possible that one or more of these hormones is responsible for the effect colostrum has on intestinal growth and matu ration. Subcutaneous injections of EGF have been shown to increase the weight, protein, DNA and enzyme activities of the intestines in mice [11] and rats [ 12,13], and the stomach weight of rats [13]. The epithelial cells of the rat intestine possess receptors for EGF [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In the rat EGF has been shown to stimulate intestinal growth when injected subcutaneously [13], have no effect on intestinal growth when given orally in formula [13], but to alter the protein/DNA ratio of colon if given orally to artificially fed rats [18]. The majority of these studies have used rats of 3-7 days of age in which the initial neonatal gut growth has already started.…”
Section: Discussionmentioning
confidence: 99%